To solve the expression \( 7 - (2 + |5 - 3|) \), we first need to calculate the absolute value part.
-
Compute \( |5 - 3| \): \[ 5 - 3 = 2 \] Therefore, \[ |5 - 3| = |2| = 2 \]
-
Next, substitute this value back into the expression: \[ 7 - (2 + |5 - 3|) = 7 - (2 + 2) \]
-
Now calculate \( 2 + 2 \): \[ 2 + 2 = 4 \]
-
Substitute this back into the expression: \[ 7 - 4 \]
-
Finally, calculate \( 7 - 4 \): \[ 7 - 4 = 3 \]
Putting it all together, the solution to the mathematical problem is: \[ \boxed{3} \]